2023
DOI: 10.1097/aln.0000000000004510
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Opioid Use and Pain Outcome and Associated Factors after Surgery under General Anesthesia: A Prospective Cohort Association Multicenter Study

Abstract: Introduction There is insufficient prospective evidence regarding the relationship between surgical experience and prolonged opioid use and pain. We investigated the association of patient characteristics, surgical procedure, and perioperative anesthetic course with postoperative opioid consumption and pain three months post surgery. We hypothesized patient characteristics and intraoperative factors predict opioid consumption and pain three months post surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
3
17
0
Order By: Relevance
“…22, 28 As noted by previous studies, patients using opioids preoperatively may be particularly vulnerable to uncontrolled pain and have a requirement for ongoing postoperative opioids. 29 Our study reinforces previous findings that opioid prescription on discharge is not independently associated with reduced pain severity, and indicates that clinicians should not prescribe opioids as a panacea for postoperative pain.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…22, 28 As noted by previous studies, patients using opioids preoperatively may be particularly vulnerable to uncontrolled pain and have a requirement for ongoing postoperative opioids. 29 Our study reinforces previous findings that opioid prescription on discharge is not independently associated with reduced pain severity, and indicates that clinicians should not prescribe opioids as a panacea for postoperative pain.…”
Section: Discussionsupporting
confidence: 89%
“…Given many patients undergoing arthroplasty are regular users of opioids in the pre-operative period, patients in this situation are at a higher risk of uncontrolled postoperative pain and chronic opioid use after surgery. 29 However, regardless of procedure, a multimodal approach to pain management is required, with preoperative assessment for high-risk pain characteristics, appropriate modulation of patient expectations, ongoing pain assessment, multimodal analgesia, non-pharmacological techniques, and pain treatment planning on discharge. 36 Preoperative counselling on pain management and opioid use may reduce patient reported pain scores, increase the likelihood of patients using non-pharmacological therapies, and increase levels of function at 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…These predictors of the new-onset pain were similar to results from cohort studies of stroke patients and patients experiencing neuropathic pain 33,34 . However, a study of the postsurgical pain found that neither patient demographics nor medical complexity (inferred from the American Society of Anesthesiologists physical status classification) were associated with the presence of pain at 3 months after surgery 35 . This null finding illustrates how, despite a general consensus that worse health is associated with the risk of future pain onset, results from prior studies are often conflicting with one another due to different populations and measures used.…”
Section: Discussionsupporting
confidence: 64%
“…33,34 However, a study of the postsurgical pain found that neither patient demographics nor medical complexity (inferred from the American Society of Anesthesiologists physical status classification) were associated with the presence of pain at 3 months after surgery. 35 This null finding illustrates how, despite a general consensus that worse health is associated with the risk of future pain onset, results from prior studies are often conflicting with one another due to different populations and measures used. By contrast, our analysis more directly demonstrated the similarities and differences in predictors of new-onset pain as compared with persistent pain within the same longitudinal survey.…”
Section: Discussionmentioning
confidence: 93%
“…In this issue of Anesthesiology , Kuck et al 3 prospectively investigated rates and predictors of prolonged postoperative surgical site pain as well as opioid use at 3 months in a cohort of patients undergoing a mix of surgical procedures. As in previous studies, 4 they found that preoperative opioid use was the strongest predictor of prolonged opioid use, with only about 4% of patients being “new” prolonged opioid users at 3 months.…”
mentioning
confidence: 99%